Compilers : Principles and Practice. - Dave, Parag H.; Dave, Himanshu B. (2012)
Compilers: Principles and Practice explains the phases and implementation of compilers and interpreters, using a large number of real-life examples. It includes examples from modern software practices such as Linux, GNU Compiler Collection (GCC) and Perl. This book has been class-tested and tuned to the requirements of undergraduate computer engineering courses across universities in India.
12.9 Testing.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2018. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books